Liquidity Risk Management: A Comparative Study between Islamic and Conventional banks of United Kingdom - Abdulle, Maimun Mohamed (2013)
According to the International Monetary Fund (IMF), Islamic banking is one of the fastest growing segments in the financial industry tracking a 10-15% growth over the past decade. One of the most important countries to development Islamic banking and finance is the United Kingdom (UK). Like their conventional counterpart, Islamic banks face a number of risk areas, which may affect their operation and performance. Liquidity risk is one example of increasing concern for the Islamic banks. However; compared to the conventional counterpart, managing and measuring liquidity risk management (LRM) is more challenging and unique for Islamic banks, due to the fact that most available conventional instruments used for liquidity risk management (LRM) are interest-based, and as a result, not sharia’ah compatible. Therefore, the core purpose of this research is to look into the liquidity risk management and to find out the factors that influence liquidity risk through a comparative study between Islamic and Conventional Banks of UK. The research is based on secondary data for the period 2007 - 2011. The research investigated net working capital (NWC), returns on equity (ROE), and the size of the bank, return on assets (ROA) and the capital adequacy ratio (CAR). The study found that liquidity risk (dependent variable) is positively related to (1) return on assets (ROA), return on assets (ROE) and (2) negatively related to the size of the banks, capital adequacy ratio (CAR) and net working capital (NWC) for Conventional banks. Whereas, liquidity risk is positively related to (1) the size of the banks, capital adequacy ratio (CAR) and net working capital (NWC) and negatively related to (2) return on assets (ROA), return on assets (ROE) for Islamic banks. In the process the research (1) identify the definitions of liquidity and liquidity risk from multinational institutions, (2) Liquidity risk management in Conventional and Islamic bank and finally, (3) examined the liquidity risk management disclosure in the annual reports of selected Islamic banks in UK.